Answer:
The value of [tex]$(f \circ g)(x)$[/tex] is [tex]$4+4 x$[/tex] and [tex]$(g \circ f)(x)$[/tex] is [tex]$4 x-16$[/tex].
Step-by-step explanation:
It is given in the question functions f(x) as 4-x and g(x)=-4x.
It is required to find [tex]$(f \circ g)(x)$[/tex] and [tex]$(g \circ f)(x)$[/tex].
To find [tex]$(f \circ g)(x)$[/tex], substitute g(x)=-4x for x in f(x) and simplify the expression.
To find [tex]$(g \circ f)(x)$[/tex], substitute f(x)=4-x for x in g(x) and simplify the expression.
Step 1 of 2
Substitute g(x)=-4x for x in f(x) and simplify the expression.
[tex]$\begin{aligned}&(f \circ g)(x)=f(g(x)) \\&(f \circ g)(x)=4-g(x) \\&(f \circ g)(x)=4-(-4 x) \\&(f \circ g)(x)=4+4 x\end{aligned}$[/tex]
Step 2 of 2
Substitute f(x)=4-x for x in g(x) and simplify the expression.
[tex]$\begin{aligned}&(g \circ f)(x)=g(f(x)) \\&(g \circ f)(x)=-4 f(x) \\&(g \circ f)(x)=-4(4-x) \\&(g \circ f)(x)=4 x-16\end{aligned}$[/tex]